Influence of Cardiovascular Risk Factors on the Prevalence of Coronary Atherosclerosis in Patients with Angiographically Normal Coronary Arteries - Bittner, Daniel O.; Klinghammer, Lutz; Schmid, Jasmin; Layritz, Christian; Hoffmann, Udo; Achenbach, Stephan; Pflederer, Tobias; Marwan, Mohamed (Academic Radiology, 2017)
RATIONALE AND OBJECTIVES: Cardiovascular (CV) disease is predominately influenced by CV risk factors and coronary computed tomography angiography (CTA) is capable of detecting early-stage coronary artery disease. We sought to determine the influence of CV risk factors on the prevalence of nonobstructive atherosclerosis in patients with normal-appearing coronary arteries in invasive coronary angiography (ICA). MATERIALS AND METHODS: In this retrospective analysis, we included 60 consecutive symptomatic patients, having undergone ICA and coronary CTA. Coronary dual source CTA was performed using electrocardiogram-triggered retrospective gated image acquisition at 40%-70% of RR interval (tube voltage 100-120 kV, tube current time product 320-440 mAs, 60 mL contrast, and flow rate 6 mL/s). RESULTS: Out of 60 patients (32 men, mean age 61 ± 11 years) with a normal coronary artery appearance in ICA, 45 (75%) patients showed atherosclerotic plaque in CTA. Plaque was present in 14 of 60 (23%) left main, 41 of 60 (68%) left anterior descending, 21 of 60 (35%) circumflex coronary arteries, and 24 of 60 (40%) right coronary arteries. More than 15% of all coronary artery segments showed detectable plaques. Interobserver agreement ranged from good to very good on a per-patient, per-vessel, and per-segment level. Patients with presence of plaque were significantly older (P = 0.005) and showed higher incidence of arterial hypertension (P = 0.019) as compared to individuals without coronary plaque in dual source computed tomography. CONCLUSIONS: The prevalence of coronary atherosclerosis by CTA is substantial in symptomatic patients with normal invasive coronary angiogram. Hypertension and older age significantly influence the prevalence of atherosclerotic plaque and highlight the importance of risk-modifying therapy.
EVALuna:33640